MENSTRUAL BLOOD PROBLEMS IN DETERMINING BID'IY DIVORCE - Muhammad Yasir (STIS Nahdlatul Ulama Aceh, 2020)
Phenomenon that occurs in society, many women who have come to know and understand about blood, this situation is very worrying because it can affect many things. One of them is divorce, where the condition of the woman who is being served affects whether or not her husband can release the divorce. The essence of the problem that the author wants to explore is the criteria for menstrual blood in the perspective of fiqh syafi`iyah and the relationship between blood and talak bid`iy in the perspective of syafi`iyyah fiqh. This research is a library research using descriptive analysis method and qualitative approach. Regarding data sources, the author only needs written data sources, namely by referring to primary and secondary sources. The primary sources of the book al-Mahalli (Kanz al-Raghibin `ala Syarh Minhaj al-Thalibin), Fath al-Wahab, Hasyiah Bujairimi` Alal-Khathiib. Meanwhile, the secondary sources of the authors take from the data that the authors search through online media or the internet. The results that the authors found; First, that blood has several criteria according to the review of fiqh shafi`iyah, these criteria are based on the age of the woman, the validity period, the character of the blood that is born which is stronger and weaker, and the condition of bleeding is normal and abnormal. Second, menstrual blood has a close relationship with bid`iy talak, because talak is only classified as bid`iy, if a person mentions his wife is right during menstruation, if it is not right during menstruation, then talak is dropped from bid`iy divorce. The author really hopes that the study that the author has described can be made new for women in particular and Muslims in general.